Blockchain-augmented digital supply chain management: A way to sustainable business - Samir Yerpude; Kiran Sood; Simon Grima (Journal of Risk and Financial Management, 2023)
The objective of this article is to assist the reader in understanding the journey from traditional Supply Chain Management to Digital Supply Chain Management. It aims to augment the concept of Digital Supply Chain Management with blockchain technology and create an extensive literature review to assist in formulating the gaps and discovering the variables that contribute towards the efficiency of a Blockchain-Based Digital Supply Chain. Moreover, this article aims to validate the impact of specified parameters resulting in customer retention and market leadership for an organization. Digital technologies such as the Internet of Things, blockchain, etc., are disrupting the traditional ways of doing business and creating value propositions for customers. Supply Chain Management is a key business process for an organization that helps them compete in the market. Organizations have seized competition not as individual brands but as supply chains. Digital Supply Chain Management is the implementation of digital technologies to capture customer data at every interaction to create customer engagement strategies. This article provides an empirical analysis of parameters influencing a Blockchain-Augmented Digital Supply Chain resulting in customer retention and market leadership and shows how, through a Blockchain-Based Digital Supply Chain, the business objective of being a customer-centric organization is assisted with the customer data generated at each interaction that is enabled.
Keywords: 650; blockchain; supply chain; supply chain management; digital supply chain management; IoT; blockchain technology; digital technologies